2010
DOI: 10.1002/mds.23046
|View full text |Cite
|
Sign up to set email alerts
|

Gaucher disease ascertained through a Parkinson's center: Imaging and clinical characterization

Abstract: Among the genes implicated for parkinsonism is glucocerebrosidase (GBA), which causes Gaucher disease (GD). Despite a growing literature that GD may present as parkinsonism, neuroimaging, olfaction and neuropsychological testing have not been extensively reported. We describe transcranial sonography (TCS), 18F-fluorodopa (F DOPA) and fluorodeoxyglucose (FDG) PET, olfaction testing, neuropsychological testing and clinical features in homozygous and compound heterozygous glucocerebrosidase mutation carriers iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 51 publications
8
74
1
Order By: Relevance
“…Similar to PINK1 17 and glucocerebrosidaseassociated PD, 16,18 but unlike PD due to parkin mutations, 15 most 8 but not all 19 LRRK2 mutation studies support the idea that olfaction is impaired in this genetic form. 8 While the degree of olfactory pathology has not been formally quantified in PD and LRRK2 PD, our clinical data support the notion that LRRK2 pathology may not be as extensive.…”
Section: Resultsmentioning
confidence: 68%
“…Similar to PINK1 17 and glucocerebrosidaseassociated PD, 16,18 but unlike PD due to parkin mutations, 15 most 8 but not all 19 LRRK2 mutation studies support the idea that olfaction is impaired in this genetic form. 8 While the degree of olfactory pathology has not been formally quantified in PD and LRRK2 PD, our clinical data support the notion that LRRK2 pathology may not be as extensive.…”
Section: Resultsmentioning
confidence: 68%
“…These studies revealed sensory-driven compensatory mechanisms in cortico-thalamo-cortical circuits (Bezard et al, 2003;Escola et al, 2003;Pessiglione et al, 2003), but it remains unclear to what extent these animal models can be generalized to human Parkinson's disease. More recently, neuroimaging studies in non-manifesting carriers of mutations known to cause monogenetic forms of Parkinson's disease, such as Parkin (PARK2) or PINK1 (PARK6) mutations (Broussolle et al, 2000;Hilker et al, 2001;Khan et al, 2002aKhan et al, , b, 2005bWalter et al, 2004;Buhmann et al, 2005;Baumer et al, 2007;Binkofski et al, 2007;Hagenah et al, 2007Hagenah et al, , 2008Schweitzer et al, 2007;van Nuenen et al, 2009a, b;Reetz et al, 2010;Saunders-Pullman et al, 2010), have been used to map cerebral changes occurring before the clinical onset of Parkinson's disease (Farrer, 2006). Non-manifesting carriers of these mutations showed structural and functional alterations similar to those observed in idiopathic Parkinson's disease, for example, nigrostriatal and premotor dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…At the Movement Disorder Center at Beth Israel Medical Center, patients with two or more Ashkenazi Jewish grandparents who met diagnostic criteria for PD were invited to participate in a genetic study of PD (Pankratz et al 2002). Consent was obtained, blood or saliva samples were collected, and DNA was isolated and screened for the eight common Ashkenazi Jewish GBA mutations (N370S, L444P, 84GG, IVS2+1G!A, V394L, del55bp, D409H, and R496H) (Saunders-Pullman et al 2010) and the leucine-rich repeat kinase 2 (LRRK2) G2019S mutation (Ozelius et al 2006). The institutional review board at Beth Israel Medical Center approved the study procedures, and all subjects provided informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…As cognitive impairment is associated with psychosis in PD and GBA mutations are associated with DLB (Nalls et al 2013;Fenelon et al 2000), it is not surprising that there is a high prevalence of hallucinations in GBA-PD (Neumann et al 2009). Cognitive impairment is also a prominent feature of PD in patients with biallelic GBA mutations (Saunders-Pullman et al 2010), but this represents a much smaller group of patients compared to those with monoallelic GBA mutations.…”
Section: Introductionmentioning
confidence: 99%